Internationalisation of construction business and e-commerce: Innovation, integration and dynamic capabilities - Thayaparan Gajendran; Graham Brewer; Malliga Marimuthu (Australasian Journal of Construction Economics and Building, 2013)
Despite the role of internet and web based applications in delivering competitive advantage through e-business process is widely acknowledged, little is done by way of research to use the dynamic capability framework, in exploring the role of ecommerce in the construction business internationalisation. The aim of this paper is to present a literature based theoretical exploration using dynamic capability view to discuss internationalising construction businesses through electronic commerce (e-commerce) platforms. This paper contextualises the opportunities for internationalising construction, using a mix of supply chain paradigms, embedded with e-commerce platforms. The paper concludes by identifying the potential of dynamic capabilities of a firm, exploiting the innovation and integration potential of different e-business systems, in contributing to the internationalisation of construction businesses. It proposes that contracting firms with developed dynamic capabilities, has the potential to exploit e-commerce platforms to channel upstream activities to an international destination, and also offers the firm’s products/services to international markets.